2020
DOI: 10.7202/1069099ar
|View full text |Cite
|
Sign up to set email alerts
|

L’appropriation des politiques d’égalité professionnelle par les acteurs : éléments de contexte et conditions

Abstract: Pour citer cet article : Coron, C. & Pigeyre, F. (2019). L'appropriation des politiques d'égalité professionnelle par les acteurs : éléments de contexte et conditions. Management international, 24(1), 127-139. * Remerciements : Nous tenons à remercier chaleureusement l'équipe de Management international, ainsi que les trois évaluateurs pour la qualité de leurs suggestions et le temps qu'ils ont consacré à cet article. 1. Nous n'indiquons que quelques références tirées d'une littérature particulièrement riche e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…For example, someone who grants more importance to gender diversity tends to implement better measures concerning this dimension than other dimensions. This finding can be explained by the fact that the implementation of gender equality policies depends on the goodwill of individuals (Coron and Pigeyre, 2019). In addition, gender equality measures can be considered to favor women, and this might lead to resistance on behalf of people who are not aware of gender inequalities (Essig and Soparnot, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, someone who grants more importance to gender diversity tends to implement better measures concerning this dimension than other dimensions. This finding can be explained by the fact that the implementation of gender equality policies depends on the goodwill of individuals (Coron and Pigeyre, 2019). In addition, gender equality measures can be considered to favor women, and this might lead to resistance on behalf of people who are not aware of gender inequalities (Essig and Soparnot, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, avoiding gender stereotypes when redacting a job offer (Laufer and Silvera, 2006), recruiting women by preference (Laufer, 2008), ensuring wage increases or that the variable parts of wages are not detrimental to women (Dickens, 1994;Lyons and Smith, 2007;Moore and Tailby, 2015), putting in place managerial coaching (Ye et al, 2015) or identifying "high-potential" female talent (Ng and Sears, 2017) require both individual and managerial action. Research shows that the involvement of the actors and their very implementation of a policy are structured by the actors' vision of gender equality, among other elements (Coron and Pigeyre, 2019). Perrier (2015) highlights that the implementation of gender equality policies is hampered by the feeling that this issue is not a priority.…”
Section: The Implementation Of Gender Equality Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our article contributes to the literature on gender equality. Indeed, the analytical grid we used to analyse and interpret our empirical material is derived from previous studies on gender equality and underlines the three issues involved in defining a gender equality policy: defining the concept of gender equality (Coron and Pigeyre, 2019; van den Brink et al, 2010); defining monitoring bodies and tools (Milner et al, 2019; Pochic and Chappe, 2019); involving local actors (Özbilgin and Tatli, 2011; Scala and Paterson, 2017). To our knowledge, the combination of this research and analytical grid has not been applied before to analyse gender equality issues.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the materials using themes corresponding to three sub-processes that characterise policy-making in the field of gender equality drawn from previous literature (1) Defining the concept of gender equality and the content of the policy. Previous research has shown that gender equality is a polysemous concept (Coron and Pigeyre, 2019), encompassing both varied dimensions (workforce diversity, wage equality, equal access to promotion, etc.) and varied action rationales, between a radical approach and a liberal approach (van den Brink et al, 2010).…”
Section: Analysis Of the Materialsmentioning
confidence: 99%